PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECK PADA KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK - Yoli Salsabila (Departemen Matematika, 2018)
The ability of mathematical communication becomes one of the abilities which is expected to be developed in mathematics learning, but the situation that occurs in the school shows that the students' mathematical communication ability can not be optimized. This is because the students have not been actively involved in the learning so that the interaction in the class is not optimal. One of the effort that can be done to improve students' mathematical communication ability and activate is by applying cooperative learning model of Pair Check type. The Pair Check cooperative learning model is used in order to help the learners to communicate their ideas both orally and in writing. The purpose of this study is to see the differences between the students who used the pair check cooperative learning model with the students who learning conventionally. The types of this research used quasi experimental (quasy experiment) with the research design of The Static Group Design. The instrument in this research is a test of mathematical reasoning ability in the form of essay matter. The results showed that the mathematical communication ability of the learners by using cooperative model of pair check type is better than the mathematical communication ability of the learners by using conventional learning in class VIII SMPN 4 Bukittinggi.Keywords – Cooperative learning type pair check, Mathematics communication skills, Conventional Learning